Perspectives on the Strategies for Teaching and Learning English as a Second Language at the University of Juba, South Sudan - Majok Mabor Matoc Apadier (RIRAI Publisher, 2020)
In line with South Sudan’s vision of a self- governing community, much hope was invested in the English speaking world thereby making a shift from Arabisation from the North. As a result, the English language was adopted a marker of identity and opposition to Arabic, language of government, education as well as international communication. As part of South Sudan’s look south policy, English was made to be a second language as opposed to a foreign language. In tandem with this country’s vision the University of Juba is not spared from the adoption of English as the language of instruction and a learning subject. Due to the democratisation of schooling and education for all, enrolment in the learning of English is increasing and resultantly large classes are emerging. In view of this, the paper therefore examines and provides preliminary results on the nature and feasibility of some teaching and learning of English in large classes at the University of Juba. This was done in light of the principles and concepts of Richards and Rodgers’ (2001) Communicative Language Teaching approach. It emerges from the findings that in the absence of a teaching framework there is no uniformity on the strategies that being adopted by both learners and teachers in the learning and teaching of English as a second language.